Strengthening Regional Fiscal Capacity in the Era of Decentralization: Strategy for Local Revenue Optimization in North Bolaang Mongondow - Lasena, Sirajudin; Aneta, Asna; Aneta, Yanti; Sulila, Ismet; Podungge, Abdul Wahab (Journal Public Policy, 2025)
This study examines strategies for optimizing Local Revenue in North Bolaang Mongondow Regency within the framework of fiscal decentralization, emphasizing efforts to strengthen regional fiscal capacity. Employing an exploratory qualitative approach, the research integrates SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to explore institutional, managerial, and personnel factors influencing the performance of Local Revenue. Data were gathered through literature review, participant observation, and in-depth interviews with key stakeholders. The findings reveal three major constraints: (1) low public awareness and compliance related to taxation and retribution systems, (2) inadequate transparency and service quality in Local Revenue management, and (3) limited competencies of government personnel in tax regulation enforcement. The study proposes three strategic approaches: market penetration through tourism and creative industry development, market development via support for micro, small, and medium enterprises and cross-sector collaboration, and product development through digital transformation of tax services and civil servant training. The results highlight the importance of institutional reform, accountable governance, and investment in human capital as integrated pathways to improve Local Revenue. Although limited in geographical and methodological scope, the study provides relevant insights for policy refinement. Future research is recommended to employ mixed methods and cross-regional comparisons to deepen understanding of the dynamics between Local Revenue management and regional fiscal independence.